1964
DOI: 10.1620/tjem.84.113
|View full text |Cite
|
Sign up to set email alerts
|

An Electromyographic Study on the Motility of Canine Stomach after Transection and End-to-end Anastomosis

Abstract: This paper reports the electrophysiologic activity of the canine stomach after transaction at various levels followed by end-to-end anastomosis. The spike discharges remain little changed when the transection line is placed in the upper third of the stomach or adjacent to the pyloric ring. When the stomach is divided and anastomosed in the corpus or the pyloric antrum 3-4 cm apart from the pyloric ring, on the other hand, the activity is considerably modified in the portion distal to the line of anastomosis. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1970
1970
2010
2010

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…The intact canine corpus and antrum in vivo show spontaneous electrical activity of approximately 5 c/min. The in vitro frequencies we recorded depended upon the location from which the strips were removed and corresponded well with the intrinsic frequencies recorded in vivo from the transacted stomach (Sugawara, 1964;Kelly & Code, 1971). In such experiments, the frequency proximal to the transaction was the same as before the transaction (5/min) whereas distally the frequency fell.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The intact canine corpus and antrum in vivo show spontaneous electrical activity of approximately 5 c/min. The in vitro frequencies we recorded depended upon the location from which the strips were removed and corresponded well with the intrinsic frequencies recorded in vivo from the transacted stomach (Sugawara, 1964;Kelly & Code, 1971). In such experiments, the frequency proximal to the transaction was the same as before the transaction (5/min) whereas distally the frequency fell.…”
Section: Discussionsupporting
confidence: 68%
“…Canine fundus circular muscle exhibited no spontaneous, myogenic electrical activity; but, in contrast, the region from the orad corpus to the pyloric ring did show spontaneous activity. Previous studies using extracellular electrodes in vivo have pointed out such differences (Kelly et al 1969;Weber & Kohatsu, 1970;Kelly & Code, 1971 (Sugawara, 1964;Kelly & Code, 1971). In such experiments, the frequency proximal to the transaction was the same as before the transaction (5/min) whereas distally the frequency fell.…”
Section: Discussionmentioning
confidence: 96%
“…In the second group of 5 dogs, we studied electromyographically the effect of pyloromyotomy on the abnormally excited pyloric portion produced by the transection of the stomach between the corpus and antrum (Sugawara 1964, Shiratori et al 1968). …”
Section: Methodsmentioning
confidence: 99%
“…Sugawara found that frequent antiperistalsis and strong hypertonic peristalsis developed in the area distal to the anastomosis when the stomach was transected at the antrum-corpus border, but not if only 2 cm or less of distal antrum remained. 9 Shiratori et al concluded that the lower transection line should be 1.5 cm proximal to the pyloric ring because no additional drainage procedure would be required at this level (Fig. 1A).…”
Section: For Gastric Ulcersmentioning
confidence: 99%